2011
DOI: 10.1007/s00468-011-0613-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and water availability alter belowground patterns of biomass allocation, carbon partitioning, and ectomycorrhizal abundance in Betula nigra

Abstract: In managed settings, seedlings are often fertilized with the objective of enhancing establishment, growth, and survival. However, responses of seedlings to fertilization can increase their susceptibility to abiotic stresses such as drought. Seedlings acclimate to variation in soil resources by reallocating carbon among different physiological processes and compartments, such as above versus belowground growth, secondary metabolism, and support of ectomycorrhizal fungi (EMF). We examined the effects of nutrient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
(83 reference statements)
3
17
0
Order By: Relevance
“…Pre‐dawn leaf water potential was measured with a PMS model 600, portable pressure bomb (PMS Instrument Co., Corvallis, OR, USA) (Kleczewski et al . ). Leaf water potential was measured weekly from the induction of the low water treatment to 2 weeks post‐egg application; however, only the measurements recorded on the first day and the final day of the water treatment were compared.…”
Section: Methodsmentioning
confidence: 97%
“…Pre‐dawn leaf water potential was measured with a PMS model 600, portable pressure bomb (PMS Instrument Co., Corvallis, OR, USA) (Kleczewski et al . ). Leaf water potential was measured weekly from the induction of the low water treatment to 2 weeks post‐egg application; however, only the measurements recorded on the first day and the final day of the water treatment were compared.…”
Section: Methodsmentioning
confidence: 97%
“…4;Ericsson 1995;Kuokkanen et al 2004;Kleczewski et al 2012). Also defoliation singly tended to cause a decrease in the ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, it has been found that leaf dry mass strongly correlates with sapwood area indicating that increased vaporization and water requirements in shoots increase conducting tissue and thus diameter and mass in stem (Kaufmann and Troendle 1981). Furthermore, as total biomass, the photosynthetically active leaf area of birch seedlings increased by fertilization, or by temperature elevation; increase in leaf area is a typical response to increased nutrients and warmth for many tree species (Maier et al 2008;Mäenpää et al 2011;Kleczewski et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions between N and drought are difficult to determine because (1) the effects can depend on the timing of N deposition relative to drought; (2) most experiments are done with young trees or herbaceous plants and not with mature vegetation; (3) many studies impose only weak drought conditions that might not result in drought-N feedbacks [74]; and (4) the impacts vary with ecosystem and plant traits. However, in general, the effects from drought and N deposition are interdependent [24] and not always additive [75,76].…”
Section: Interactions Between N and Droughtmentioning
confidence: 99%